Passport data quality assessment framework for CGIAR Genebanks - Giraldo, Norma; Mendez, Andres; Diaz, Maria Victoria; Sosa, Chrystian; Gonzalez, Arturo; Llanos Herrera, Lizeth; Kehel, Zakaria; Ramirez Villegas, Julian (2024)
This report presents a methodological framework to assess the quality of geographic and taxonomic data in CGIAR genebanks. It introduces two indices, Geographical Quality Score (GQS) and Taxonomic Quality Score (TQS), to diagnose data reliability. The system integrates external databases for validation and features an interactive dashboard for usability. Results guide genebank curators in data curation and strategic improvements, ensuring better utilization of germplasm resources.